The Role of Algae and Cyanobacteria in Arid Lands: a Review - Isichei, Augustine O. (2014)
Algae, cyanobacteria, and lichens occur in surface cryptogamic crusts, as free-living organisms in water bodies and within or on rocks in arid lands. The possible roles algae, cyanobacteria, and lichens could play in arid environments include physical improvement and protection of the soil, contribution of nitrogen to the arid ecosystem by nitrogen-fixing cyanobacteria and lichens, and primary biomass production for use as food and other secondary production. Physical improvement and protection of arid soils has potential in controlling desertification and rehabilitating arid lands. Culturing algae and cyanobacteria for biomass production, already being utilized in nonarid environments in agriculture, acquaculture, and now in the biochemical industry, has bright prospects in arid areas with their abundant sunshine. Primary production by the organisms can also be used for direct human and livestock consumption and in urban waste treatment. Biomass production can thus act as a means of resource diversification and therefore relieve pressure on fragile arid lands.